Caries formation around restorative composite and glass ionomer cement - Okida, Ricardo Coelho [UNESP]; Rahal, Vanessa [UNESP]; Goiato, Marcelo Coelho [UNESP]; Okida, Daniela Secches da Silveira [UNESP] (My University, 2014)
This in vitro study evaluated the demineralization around restorations class V made on the buccal and lingual surfaces of teeth when using different restorative materials. Thirty extracted teeth were randomly divided into 3 groups (n=10) according to the restorative material: Group I - Fuji II LC (GC America Inc., Alsip, Illinois, USA), Group II - Tetric (Ivoclar Vivadent AG, Schaan, Liechtenstein) and Group III - Chelon Fil (3M/ESPE., Seefeld, Germany). The teeth were submitted to a pH-cycling model associated to a thermocycling model. Sections were made and the specimens were analyzed under a polarized light microscopy as for the presence of demineralization. Measurements were performed and the results were subjected to statistical analysis using Anova and Tukey´s Test (α=0.05). Mean values of demineralization depth (µm) according to each positions showed that the demineralization was significantly reduced when Chelon Fil (Group III) was used for all depths, when compared to fluoridated resin materials. Also, it was verified that non-fluoridated resin material, composite resin Tetric, had the lowest inhibitory effect on the development of demineralization.

Este estudo in vitro avaliou a desmineralização ao redor de restaurações classe V realizadas nas superfícies vestibular e lingual dos dentes com diferentes materiais restauradores. Trinta dentes extraídos hígidos foram aleatoriamente divididos em 3 grupos de estudo de acordo com o material utilizado: Grupo I - Fuji II LC (GC America Inc., Alsip, Illinois, USA), Grupo II - Tetric (Ivoclar Vivadent AG, Schaan, Liechtenstein) e Grupo III - Chelon Fil (3M/ESPE., Seefeld, Germany). Os dentes foram submetidos a diferentes variações de pH associadas à termociclagem. Os espécimes foram então preparados e seccionados para análise em microscopia óptica sob luz polarizada quanto à presença ou não de desmineralização. Asmensurações foram realizadas e os resultados foram submetidos à análise estatística utilizando o Anova e Teste de Tukey (á=0,05). Os valores médios da profundidade de desmineralização (µm) de acordo com cada posição analisada mostrou que o material Chelon Fil (Grupo III) apresentou redução significativa de desmineralização em todas as profundidades, quando comparado com os materiais resinosos com fluoretos. Além disso, observamos que para o material resinoso sem fluoreto, como a resina Tetric, foram verificados os menores efeitos inibitórios no desenvolvimento de desmineralização.
Formação de cárie ao redor de compósitos restauradores e cimento de ionômero de vidro
Keywords: Fluorides; Demineralization; Microscope; Fluoretos; Desmineralização; Microscópio